If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 5 + 3x = 26 Reorder the terms: 5 + -6x + 3x = 26 Combine like terms: -6x + 3x = -3x 5 + -3x = 26 Solving 5 + -3x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 26 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 26 + -5 -3x = 26 + -5 Combine like terms: 26 + -5 = 21 -3x = 21 Divide each side by '-3'. x = -7 Simplifying x = -7
| 77-a=12 | | 5y^2-8y=3 | | 4(-2x+5)=-26 | | (x*4)+6=18 | | 20x^3+6x^2-2x+1=0 | | 2(3+2x)=-26 | | -6(2.4+0.4y)-2y=-14 | | X^2-2kx+3k+2=0 | | -6(2.4+-0.4y)-2y=-14 | | (x-8)(x-3)=30 | | .75(20+6y)-.5(18-9y)= | | N+N=N(n) | | Z^2-z+1-i=0 | | 5x-10y-2=0 | | 7m+5=21-3m | | 6(2.92)-3y=14 | | 4x^2+16-18=0 | | 2x^3+5X-18=0 | | 5-7(12)-15= | | 3(m-6)=6(m-1) | | (3+5i)(2+3i)(7+4i)=0 | | -2(X-4)+5x=2(X+3)+X+3 | | 5x^2-9x-2=o | | 2x+4-5=3x+1 | | 5[8+(81)]= | | f+12=4 | | f+12=-4 | | 6x-3(7-2x)=14 | | 5-7.12-15= | | (9(m+5)-15)+(2(m-3)+4)= | | 6(7au)+u=36+u | | 3x-3(5-2x)=3 |